The Effect Of Digital Transformation Readiness, Data Governance Maturity And Responsiveness Of It Support On Digital Trust In Educational Institutions - Hadi Prayitno; Dhian Supardam; Syahri; Mustangin; Sinta Julina; Apriani Riyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The study's principal goal is to explore the link among the three factors, which are digital transformation readiness, data governance maturity, IT support, and the dependent variable trust in digital technology used in educational institutions. The research context is the digital systems applied in the educational sector and the user trust requirement in technology-based services. The research is done with a quantitative explanatory approach on 150 respondents, made up of educators and education staff, who were selected purposely. A five-point Likert scale questionnaire is employed to collect data, and multiple linear regression is used for data analysis. The findings indicate that all three factors-digital transformation readiness, data governance maturity and IT support responsiveness- were positively and significantly associated with digital trust. This research has contributed to the literature on educational management and information systems by incorporating the process of digital trust development in the educational sector. Besides, one of the key practical implications of the research is that educational institution leaders should always regard trust and sustainability while devising the policies related to the three areas mentioned above, i.e., digital transformation, data governance, and information technology services.